Strategi Pemasaran Produk Olahan Jamur Tiram pada Kelompok Wanita Tani (KWT) Spora Bali - NL. Budasih; IGAA. Ambarawati; NW. Sri Astiti (JURNAL MANAJEMEN AGRIBISNIS, 2014)
Agriculture sector is an important sector because of this sector most of human needs met. The development of horticultural commodities is driving diversification program, extensification, intensification, and rehabilitation of agriculture which is the core of the agricultural development activities. The processing is very important to be extend the usefulness of commodity oyster mushrooms and increase the economic value of the product. This study aims to determine the constraints faced by farmers of oyster mushroom cultivators as well as manufacturers of processed oyster mushrooms products belonging to the Group of Women Farmers (KWT) Spora Bali. Respondents intentionally set, including the chairman and members of the Bali Spora Women Farmers Group, PPL, and regular consumers from Pradnyagama autism children Foundation. Internal and external factors are identified and analyzed by SWOT analysis to determine some alternative strategies accordingly. Furthermore, alternative strategies are analyzed by QSPM to determine strategic priorities. The results of the research show that based on internal analysis, oyster mushroom processing business of KWT Spora Bali is on the average position in the harness strengths and weaknesses. The main strength of KWT Spora Bali is in the product variation. The main weakness of KWT Spora Bali is the selling price of the product. Based on the analysis of the external environment, oyster mushroom processing business of KWT Spora Bali is taking advantage of the opportunities to overcome the threats faced by KWT Spora Bali. The main opportunity KWT Spora Bali is rising customer demand. As for the main threat of KWT Spora Bali is rising a production cost. SWOT Analysis discover 6 alternative strategies namely: open opportunities for cooperation with other parties associated with the distribution of products, increased sales promotion or dissemination of products information, to improve the appearance of products through improved packaging, looking for market information by using information technology, trying to maintain product quality and increase efficiency and effectiveness in marketing the product. QSPM analysis results show that the strategy is a top priority to improve the appearance of products through improved packaging for products produced. This strategy can be done by updating the design, colors, and include a brand that has been established along with the expiration date and licenses from the Ministry of Health so that the product becomes more attractive which will increase the selling price of the product and can expand the marketing area.